2023
DOI: 10.3847/1538-4357/acd558
|View full text |Cite
|
Sign up to set email alerts
|

Over 500 Days in the Life of the Photosphere of the Type Iax Supernova SN 2014dt

Abstract: Type Iax supernovae (SNe Iax) are the largest known class of peculiar white dwarf SNe, distinct from normal Type Ia supernovae (SNe Ia). The unique properties of SNe Iax, especially their strong photospheric lines out to extremely late times, allow us to model their optical spectra and derive the physical parameters of the long-lasting photosphere. We present an extensive spectral timeseries, including 21 new spectra, of SN Iax 2014dt from +11 to +562 days after maximum light. We are able to reproduce the enti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…The present spectral synthesis covers a longer time, ∼90 days after the maximum. Camacho-Neves et al (2023) showed that radiative transfer codes that assume a blackbodyemitting photosphere can reproduce most of the spectral features and their evolution over years after the explosion because type Iax SNe never show a fully nebular spectrum. At the same time, spectral synthesis is less sensitive to the exact mass fractions of chemical elements at t 30 exp > days than at the earlier epochs.…”
Section: Spectral Modeling With Tardismentioning
confidence: 99%
See 1 more Smart Citation
“…The present spectral synthesis covers a longer time, ∼90 days after the maximum. Camacho-Neves et al (2023) showed that radiative transfer codes that assume a blackbodyemitting photosphere can reproduce most of the spectral features and their evolution over years after the explosion because type Iax SNe never show a fully nebular spectrum. At the same time, spectral synthesis is less sensitive to the exact mass fractions of chemical elements at t 30 exp > days than at the earlier epochs.…”
Section: Spectral Modeling With Tardismentioning
confidence: 99%
“…The abundance tomography presented in this study is split into two parts: before t 30 exp = days from the date of explosion (hereafter referred to as early epochs), we follow the standard technique for synthesizing a spectral time series (Singh et al 2023), while for the later epochs, a simplified method is adopted similar to that of Camacho-Neves et al (2023). For both phases, the same time of the explosion (t JD 2459116.3 exp =…”
Section: Spectral Modeling With Tardismentioning
confidence: 99%